Oxytocin Hormone Induction on Milk Production in Relation to Dairy Kid Performance - Sumaryadi, Mas Yedi; Saleh, Dadang Mulyadi; Nugroho, Aras Prasetiyo; Hidayat, Nu'man; Hidayah, Chomsiatun Nurul (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
The application of oxytocin induction to milk production in relation to the performance of kids in dairy goats had been carried out in the